Normative Analysis of Article 14 of Permendagri Number 72 of 2022 in its Implementation in Bandung Regency - Sultan Aulya Rachman; Muhammad Asro; Aji Saptaji (Hakamain: Journal of Sharia and Law Studies, 2025)
This research analyzes the effectiveness of the implementation of Digital Population Identity (Identitas Kependudukan Digital/IKD) based on Article 14 of the Regulation of the Minister of Home Affairs No. 72 of 2022 in Bandung Regency from the perspective of Siyasah Dusturiyah. The research employs an empirical juridical method by collecting interview data, IKD activation data, relevant legal sources, as well as related literature and academic journals. The collected data are analyzed descriptively. The findings indicate that the implementation of IKD has achieved internal effectiveness, particularly in accelerating population administration services and ensuring data security through proactive service strategies. However, the implementation faces critical external challenges, namely the rejection of IKD by third parties such as banks and financial institutions, as well as infrastructure limitations, including the requirement for personal devices and inadequate network connectivity. From the perspective of Siyasah Dusturiyah, the IKD policy aligns with the principle of public welfare (maslahah) through efficiency and data protection; nevertheless, these external constraints threaten the fulfillment of daruriyah, hajiyah, and tahsiniyah aspects in the equitable delivery of public services